“Try something else!” — When users change their discursive behavior in human-robot interaction - Lohse, Manja; Rohlfing, Katharina; Wrede, Britta; Sagerer, Gerhard
This paper investigates the influence of feedback provided by an autonomous robot (BIRON) on users’ discursive behavior. A user study is described during which users show objects to the robot. The results of the experiment indicate, that the robot’s verbal feedback utterances cause the humans to adapt their own way of speaking. The changes in users’ verbal behavior are due to their beliefs about the robots knowledge and abilities. In this paper they are identified and grouped. Moreover, the data implies variations in user behavior regarding gestures. Unlike speech, the robot was not able to give feedback with gestures. Due to the lack of feedback, users did not seem to have a consistent mental representation of the robot’s abilities to recognize gestures. As a result, changes between different gestures are interpreted to be unconscious variations accompanying speech.
Keywords: discursive behavior; autonomous robot; BIRON; man-machine systems; robot abilities; robot knowledge; user gestures; robot verbal feedback utterance; speech processing; user verbal behavior; service robots; human-robot interaction; human computer interaction; gesture recognition